2018
DOI: 10.1158/1078-0432.ccr-18-1100
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Suppression and Increased Phosphorylated STAT3 in Regulatory T Cells are Associated with Benefit from Adjuvant PD-1 Blockade in Resected Metastatic Melanoma

Abstract: PD-1 blockade induces durable responses in patients with metastatic melanoma and prolongs relapse-free survival in patients with resected melanoma; however, current biomarkers do not consistently associate with patient responses. In this study, we investigated the impact of nivolumab therapy on peripheral blood regulatory T cells (Treg) and its relation to patient outcomes. Peripheral blood Tregs and conventional CD4 T cells from patients with resected high-risk melanoma treated with adjuvant nivolumab were as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 46 publications
5
43
1
Order By: Relevance
“…In contrast, Tarhini et al [ 118 ] observed an increase of Tregs and improved PFS in 6 weeks of neoadjuvant ipilimumab therapy. In agreement with this study, Woods et al [ 119 ] reported increased Treg frequency in the group of melanoma patients responding to nivolumab therapy. The opposite changes in Treg frequency in the tumor microenvironment (TME) and in the blood that question their functional activity and increased phosphorylation of signal transducer and activator of transcription (STAT) in Tregs of responding patients can be a possible explanation of these contradictory findings [ 118 , 119 ].…”
Section: Predictive Biomarkers Related To the Host Immune Systemsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, Tarhini et al [ 118 ] observed an increase of Tregs and improved PFS in 6 weeks of neoadjuvant ipilimumab therapy. In agreement with this study, Woods et al [ 119 ] reported increased Treg frequency in the group of melanoma patients responding to nivolumab therapy. The opposite changes in Treg frequency in the tumor microenvironment (TME) and in the blood that question their functional activity and increased phosphorylation of signal transducer and activator of transcription (STAT) in Tregs of responding patients can be a possible explanation of these contradictory findings [ 118 , 119 ].…”
Section: Predictive Biomarkers Related To the Host Immune Systemsupporting
confidence: 90%
“…In agreement with this study, Woods et al [ 119 ] reported increased Treg frequency in the group of melanoma patients responding to nivolumab therapy. The opposite changes in Treg frequency in the tumor microenvironment (TME) and in the blood that question their functional activity and increased phosphorylation of signal transducer and activator of transcription (STAT) in Tregs of responding patients can be a possible explanation of these contradictory findings [ 118 , 119 ]. Altogether these results suggest that not only the frequency of cells, but also their immunosuppressive potential and activity are relevant to the occurrence of response.…”
Section: Predictive Biomarkers Related To the Host Immune Systemsupporting
confidence: 90%
“…These changes were largely distinct with only <5% overlap in significantly changed immunophenotypes. Taken with data presented showing a lack of overlap in outcome-associated immunophenotypes between the two cohorts/treatments and published literature 6,7,8,9 it is increasingly clear that the systemic immune impact and the mechanisms by which CTLA4 and PD1 blockade function are distinct.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, there are few biomarkers associated with response to both αPD1 and αCTLA4. For some biomarkers, such as TCR diversity, T-cell memory subsets and frequency of circulating Tregs, there is a reciprocal association with response for the two therapies 6,7,8,9 . While useful for identifying rational targets for combination therapy, these biomarkers have failed to stratify patient responses well enough to have clinical utility for prediction of outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation for these discrepancies may lay on the varying suppressive capacities of Tregs following ICI therapy. For example, Woods et al found that metastatic melanoma patients responding to nivolumab showed an increase in circulating Tregs, but these cells had increased phosphorylated STAT3 which correlated with reduced immunosuppressive activity [39].…”
Section: Cd4 T Cellsmentioning
confidence: 99%